Analysis of the Influence of Incorporating Different Thermal-Insulating Materials into the Sub-Ballast Layers - Libor Ižvolt; Peter Dobeš; Martin Mečár; Deividas Navikas (Buildings)
Adverse climatic conditions, particularly excessive water and frost, necessitate the design of thick protective sub-ballast layers when dealing with frost-susceptible subgrade surfaces, especially when using standard natural materials (crushed aggregate or gravel–sand). Given the current preference for conserving natural construction materials and promoting sustainable development in the dimensioning of sub-ballast layers, it is advisable to incorporate various thermal insulation, composite, or suitable recycled materials in their design. Therefore, the paper analyses the impact of incorporating different thermal insulation materials (including extruded polystyrene, Liapor, Liapor concrete, and composite foam concrete) into sub-ballast layers. As part of the experimental research, these modified sub-ballast layers were constructed on a real scale in the outdoor environment of the University of Žilina (UNIZA) campus. They were subsequently compared in terms of their thermal resistance to climatic loads. The research results demonstrate that extruded polystyrene provides the optimal thermal insulation effect in modified sub-ballast layers, which was subsequently used in the numerical modelling of railway track structure freezing under different climatic loads.